Smallholder and village milk processing in the highlands of Ethiopia - O'Connor, C.B. (Food and Agriculture Organization of the United Nations, 1994)
Ethiopia has the largest cattle population (30 million) of any country in Africa. There are about 3.7 milking cows with an average yield of about 210 kg per annum. Comparative data for other African countries is provided. Milk utilisation by rural milk producers is centred around the processing of butter and a cottage type cheese from milk which is surplus to the liquid requirements of the family. Butter is made from naturally soured whole milk using the traditional clay pot and the cheese (ayib) is made from the buttermilk. The butter and cheese are sold at the market and household goods are purchased with the monies received. There is a state-owned milk collection, processing and marketing enterprise (DDE) but milk producers in remote areas do not have access to this collection service. Where possible farmers would prefer to process their own milk rather than sell it to DDE mainly for reasons of price. A user group for milk processing has been established by the Ministry of Agriculture in a rural area about 140 km north of Addis Ababa. The membership of the group is 32 with a potential membership of about 100. Members must supply a minimum of 2 litres per day for which they are paid 0.75 EB (5EB=1USD) per litre. Butter and cheese are made and sold to the local community. Milk intake ranges from about 900 litres to 200 litres per month. A net profit of 607 EB was made during the year 1991/1992. It is suggested that with proper care and nurturing this users group will provide the necessary example and impetus for other users groups and will lead to the Development of the milk production and processing industry.